Pengaruh Komponen Destinasi Wisata Terhadap Kepuasan Wisatawan - Andy Mulyana; Ida ayu Made Er Meytha Gayatri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This research aims to know the influence of the Attraction, Amenity, Accessibility, Ancilliary on tourist satisfaction. This type of research is descriptive with a quantitative approach with a total of 93 respondents. The technique of answering data using a questionnaire. For statistical tests and the processing of data is carried out by using the Partial Least Square (SmartPLS 3.0). The results of the study indicate that simultaneously, the variables of Attraction, Amenity, Accessibility, Ancilliary, together affect tourist satisfaction. While partially the Attraction variable has a significant effect on tourist satisfaction with a value of 3.75. Amenity variable has a significant effect on tourist satisfaction with a value of 2.29. Accessibility variable has a significant effect on tourist satisfaction with a value of 3.30. Ancilliary variable has no significant effect on tourist satisfaction with a value of 0.53. While the coefficient of determination (R2) of 0.83 means that Attraction, Accessibility, Amenities, and Anciliaries have an influence of 0.83% on satisfaction while the remaining 17% is influenced by other variables that were not examined in this study.